The impact of neighborhood social and built environment factors across the cancer continuum: Current research, methodological considerations, and future directions. Issue 14 (6th April 2015) - Gomez, Scarlett Lin; Shariff‐Marco, Salma; DeRouen, Mindy; Keegan, Theresa H. M.; Yen, Irene H.; Mujahid, Mahasin; Satariano, William A.; Glaser, Sally L.
Abstract : Neighborhood social and built environments have been recognized as important contexts in which health is shaped. The authors reviewed the extent to which these neighborhood factors have been addressed in population‐level cancer research by scanning the literature for research focused on specific social and/or built environment characteristics and their association with outcomes across the cancer continuum, including incidence, diagnosis, treatment, survivorship, and survival. The commonalities and differences in methodologies across studies, the current challenges in research methodology, and future directions in this research also were addressed. The assessment of social and built environment factors in relation to cancer is a relatively new field, with 82% of the 34 reviewed articles published since 2010. Across the wide range of social and built environment exposures and cancer outcomes considered by the studies, numerous associations were reported. However, the directions and magnitudes of associations varied, in large part because of the variation in cancer sites and outcomes studied, but also likely because of differences in study populations, geographic regions, and, importantly, choice of neighborhood measures and geographic scales. The authors recommend that future studies consider the life‐course implications of cancer incidence and survival, integrate secondary and self‐report data, consider work neighborhood environments, and further develop analytical and statistical approaches appropriate to the geospatial and multilevel nature of the data. Incorporating social and built environment factors into research on cancer etiology and outcomes can provide insights into disease processes, identify vulnerable populations, and generate results with translational impact of relevance for interventionists and policy makers. Cancer 2015;121:2314–2330. © 2015 American Cancer Society . Abstract : Neighborhood social and built environments have been recognized as important contexts in which health is shaped. The literature relating various cancer outcomes to neighborhood social and built environment factors is reviewed, and the authors discuss methodological considerations for this area of research.